Pseudocapacitive batteries: Methods of activating quantized capacitance energy storage mechanism - Yee Wei Foong (Invention Disclosure)
The invention embodies a method to incorporate nanoparticles in an energy storage device, more specifically batteries and supercapacitors, to enable quantized capacitance energy storage mechanism. It operates on the principle of quantization in nanoscale, also referred to as the solvated Coulomb blockade mechanism, rather than the classical intercalation mechanism, allowing greater electron storage potential within the nanoparticles relative to classical energy storage devices. This enables pseudocapacitive battery to theoretically store as much energy as lithium-ion batteries while all its other properties resemble ultracapacitors, including the theoretical ability to have long cycle life and can be charged and discharged at very high rates, a significant departure from lithium-ion battery technology which are well known to have long charging times. This invention also enables electrochemical storage devices to be designed with sustainable materials (e.g., carbon), transitioning from the heavy reliance on precious metals (e.g., lithium, manganese, cobalt, and nickel).